Rainfall and dew water harvesting for sanitary use on a metalurgy industry (Bom Jardim – RJ, Brazil) - Dumingues , Elaide; Sato , Anderson Mululo; Finotti, Ricardo (Technical and Scientific Journal Green Cities, 2024)
This study evaluates a Rain Water Harvesting (RWH) system considering its social, economic, and ecological aspects. We constructed a prototype at a metallurgical industry in Bom Jardim municipality, Rio de Janeiro state, Brazil, that uses rain water for sanitary purposes. The prototype has the same characteristics of the industry roof such as materials, positioning, and similar inclination. The rainfall and runoff volume were measured and water was also collected in periods when there was no rainfall to assess the amount of atmospheric water condensation collected (dew water). A thermo-hygrometer was used to note the local air relative humidity and temperature every day. We also conducted a survey on the costs to build the entire system and applied a survey to it employees, to estimate water savings. Collected rainwater was analyzed to the following parameters: turbidity, pH, nitrate, nitrite, orthophosphate, silicate, ammonia, organic matter, total coliform and E. coli. The roof had a mean flow coefficient of 88%, which resulted for the roof area (3,940m²) a mean of 28,354.04±44,674.86L. The uptake of water by atmospheric condensation can reach 2,469 liters on a day and it is positively correlated with the minimal temperature. The system payback time was estimated in 10 years. However, given the quality of the water, this system could be in use for other purposes, which would increase water savings and reduce the payback time.
Keywords: water economy; dew condensation; water quality